2001
DOI: 10.1557/proc-688-c4.24.1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Surface Crystalline Quality of an Epitaxial (100)ZrN Film as a Bottom Electrode Diffusion Barrier for Ferroelectric Capacitors

Abstract: We fabricated the double epitaxial layers of Ir on barrier metal ZrN for Pb(ZrxTi1−x)O3 (PZT), using reactive sputtering. In order to remove the surface oxide layer of the ZrN film prior to depositing the Ir film, we used a new treatment method, in which the ZrN film is dipped into a 0.5% buffered HF solution for less than 30 seconds and then immediately dipped into a hydrazine (N2H4) monohydrate solution for 60 seconds. Also, in order to suppress the generation of twin boundaries and to improve crystalline qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Although the obtained FWHM value (3.0 ) is somewhat larger than that of a 200nm-thick epitaxial ZrN film grown on a (001)MgO substrate at 450 C by pulsed laser deposition, 18) the value is comparable to that of a 100-nm-thick epitaxial ZrN film grown on a (001)Si at 850 C by rf reactive sputtering. 4) It is therefore expected that these ZrN films may be grown epitaxially.…”
Section: Single-oriented Growth Of Zrn Filmmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the obtained FWHM value (3.0 ) is somewhat larger than that of a 200nm-thick epitaxial ZrN film grown on a (001)MgO substrate at 450 C by pulsed laser deposition, 18) the value is comparable to that of a 100-nm-thick epitaxial ZrN film grown on a (001)Si at 850 C by rf reactive sputtering. 4) It is therefore expected that these ZrN films may be grown epitaxially.…”
Section: Single-oriented Growth Of Zrn Filmmentioning
confidence: 99%
“…ZrN films have attracted much attention for various applications such as diffusion barrier material used in Cu metallization technology for the production of Si-LSI devices, and the hard coating material of cutting tools, because of their high hardness, high thermal and chemical stabilities and low resistivity. [1][2][3] For example, Horita et al 4) recently reported the following. For an integrated ferroelectric random access memory (FeRAM) with a stacked capacitor cell structure, a direct electrical contact must be formed from the source of the transistor to the bottom of the capacitor via a conducting barrier layer which prevents reaction between the ferroelectric film and the Si substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation